Fenomena Tiktok di Negeri Syariah: Dampak terhadap Perilaku Remaja Kota Langsa - Samsuar; Gandhi, Almutia; Syahri, Adhari; Zulkarnain, Zulkarnain (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2023)
The TikTok application, video social platform supported by music. Whether it's dance music, freestyle, or performance. Makers are encouraged to be as creative as possible and imagine freely and express their expressions by using this application. This application is also currently very popular with teenagers. This study aims to determine the effect of using the TikTok application on the behavior of teenagers in Langsa City. In this study, the sample taken by researchers was 59 respondents. This research uses quantitative research methods. The technique used in this study is Nonprobability Sampling. Data collection techniques using a questionnaire (questionnaire). The data analysis technique used in this research is product moment and hypothesis testing. Based on the results of the study, it was found that thecalculated 21.019 > Ftable 2.002. Shows the value of Sig. 0.000 <0.05 then, it is certain that there is an influence between the independent variable (X) on the related variable (Y) in this study. Then it is known that the value of the Pearson correlation is 0.519 with a sig. (2-tailed) 0.000. Obtaining this score means that the variable that influences the use of the Tiktok application has a correlation with the child's behavior variable with a value of 0.519 . moments)